Aorta–Left Renal Vein Fistula in a Woman - Yagdi, Tahir (2004)
Spontaneous rupture of an abdominal aortic aneurysm into a retroaortic left renal vein is an uncommon occurrence. A 55-year-old woman presented with shortness of breath, vomiting, and diffuse abdominal pain that had radiated to her back and legs for the preceding 10 days. A pulsatile abdominal mass, hematuria, renal insufficiency, and heart failure were present at the initial evaluation. Computed tomography showed an infrarenal abdominal aortic aneurysm that communicated with a retroaortic left renal vein. After urgent surgical repair, cardiac and renal function were dramatically improved. To the best of our knowledge, this is the 1st reported case of a woman with such a fistula. We review treatments reported in the literature.